Riwayat Waktu Percepatan Sintetik Untuk Situs Kelas Sc Kota Padang - Delfebriadi, Delfebriadi (Jurnal Bangunan, Konstruksi & Desain, 2024)
This paper presents a study of seismic hazards in Padang city. Referring to the literature of the September 2009 Padang earthquake, a synthetic acceleration time history was created based on the stochastic method and wave scaling technique for a planned earthquake scenario using the SMSIM v2.3 program. The final result obtained is a synthetic acceleration time history for a class Sc site according to SNI 1726-2019 with a design earthquake criterion of a building age of 50 years and a probability value of 2% exceeded.